WAKALAH WALI NIKAH DI KECAMATAN DUMBO RAYA PERSPEKTIF HUKUM ISLAM - Abdur Rahman Adi; Ahmad, Ahmad Maulana (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
Abstract This study aims to analyze the understanding of the Muslim community in Dumbo Raya District regarding marriage wakalah and how Islamic law reviews its application in the sub-district. This type of research is qualitative, while the approach used is phenomenological and empirical juridical approaches. Research data sources come from primary data sources in the form of certain informants who are considered capable with the term research object, data collection techniques in the form of observation, interviews, and documentation, while data processing and analysis techniques through editing, classification, verification, Miles and Huberman model analysis, presentation data, conclusion / verification. The results of the study show that the majority of the local community's understanding of the wakalah wali issue in marriage contracts is not based on their knowledge of this matter, but this understanding is based on how the wakalah wali practice has become a habit in society. In principle, the application of the Wakalah guardian practice in the marriage contract of the Islamic community in Dumbo Raya District is not contrary to Islamic law. Even though it is not a problem if a guardian delegates his guardianship rights to other people, what is of concern to researchers is not to have guardians from so many orderly guardians. who are actually able to become guardians but because of the habits adopted by other communities so that the urgency of the position of guardian is not much utilized. Keywords: Wakalah, Marriage Guardian, Islamic Law